Development of an Ion Chromatography Method for the Determination of Organic Impurities in Ferumoxytol - Deepala, Naga Sankara Rao; Pedapalli, Sasikanth; Jagadeesh, Kantamsetti; Islam, Mohammad Shahidul; Gadipelli, Prakash; Dahlous, Kholood A.; Alam, Mahboob; Raju, Rudraraju Ramesh (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim: To the development of an ion chromatography method for the determination of organic impurities in Ferumoxytol. Materials and Methods: A new ion chromatographic method was employed for the precise and suitable quantification of organic impurities in Ferumoxytol drug. Specifically, LOD, LOQ, Linearity, and Accuracy evaluations were conducted to thoroughly validate each of these areas. Results: All the studied carbohydrate impurities showed linear ranges within 0.0005 to 0.0030 mg/mL with the correlation coefficients higher than 0.9991. The limits of detection were all less than 0.0002 mg/mL. The limits of quantification were all less than 0.0006 mg/mL. The RSDs of the method were less than 3%. Conclusion: This method showed a lot of promise for precise impurity testing in Ferumoxytol drug substance, improving pharmaceutical quality assurance and making sure that patients are protected.
Keywords: Ferumoxytol; Ion Chromatography; Method Development; Organic Impurities; Pharmaceutical Analysis